التصميم الإبداعي للخامات البيئية في التغليف من منظور اقتصادي - أبو الغيط، هايدي يوسف (الجمعية العربية للحضارة والفنون الإسلامية, 2021)
تعتبر منظومة التعبئة والتغليف عنصر أساسي في تمكين المنتج من المنافسة في الأسواق العالمية باعتبار أن التعبئة السليمة الواجهة الأولى للسلعة التي يتلقاها المستهلك لأول وهلة، فمما لا شك فيه إن التعبئة والتغليف حاجة ضرورية ولازمة لأي تبادل تجاري للسلع، حيث تعد نظم التغليف عالم من الإبداع في ميادين تطوير خصائص الخامات المتعارف عليها في التغليف، كما أنه يتوقف على الخصائص الاقتصادية والبيئية للخامات الداخلة فيه. حيث أن حسن التعامل مع مواد التعبئة والتغليف وتدويرها للحفاظ على البيئة وتعزيز الاقتصاد هو أحد المؤشرات الحضارية في العالم والتي تهدف بشكل أساسي إلى إيجاد أو تحسين مواد للتغليف غير الضارة بالبيئة قدر الإمكان ذات مردود اقتصادي، وأيضا التوجه نحو استحداث أساليب وطرق جديدة لتدوير المخلفات لمواد التعبئة والتغليف. حيث أصبحت التعبئة والتغليف وسيلة هامة لتسويق المنتجات والتأثير على خيارات المستهلك، وفي مجال الأغذية مثلا، نجد أن هناك طرق عديدة يتم بناء الفكرة للتغليف على متطلبات التسويق القائمة على فكرة العبوات الصحية، مما يؤثر على قناعة الناس وتوقعاتهم الصحية، وتجربتهم الحسية، واستهلاكهم. حجم وشكل العبوات والحاويات تؤثر على حجم الاستهلاك من خلال تغيير تصور الناس عن مقدار الطعام الذي يتم تقديمه، ومقدار ما يأكلونه. ولأن الخامة هي وسيلة التعبير الفني الوظيفي، فهي تكسب التغليف المعاني والقيم الجمالية ويمكن أن تتحول إلى وسيلة إعلانية، إذا تم الاستفادة منها عمليا، وتم تحويلها إلى شيء له قيمة جمالية ووظيفة، بحيث يستطيع المصمم من خلالها أن يستغل الخصائص البيئية للخامات المتنوعة ويستخدمها وفق الاحتياج التصميمي. تنبع المشكلة البحثية من الحاجة لتحقيق الاستفادة بتوظيف الخامات البيئية المحلية بمنظور اقتصادي بحيث تحقق قيم إبداعية وتصميمية مميزة. يهدف البحث إلى تسليط الضوء على أسس التصميم الإبداعي للخامات البيئية في التغليف من منظور اقتصادي."
The packing and packaging system is an essential factor in enabling the product to compete in international markets, considering that the appropriate packaging is the first impression that the consumer receive. Thus, packing and packaging are undoubtedly an important and required necessity in any product commercial exchange; packaging systems have a world of creativity in the field of improving the features of the commonly used packaging materials, as it depends on the economic and environmental features of these materials. Handling packing and packaging materials properly; as well as recycling them to preserve the environment; is one of the international civilized indicators that mainly aims to find or develop as much packaging materials; which are environmentally friendly and economically rewarding; as possible, also, attempting to create new methods and ways to recycle these materials as well. Packing and packaging have become a crucial tool in marketing the product and influence the consumers choices, in the food industry for instance, we find that that there are many methods on which the creation of the ideas for packing is based, such as the idea of healthy packing which impacts people’s convictions, their health expectations, sensory experience and consumption, as the size and shape of packs and containers affect the size of consumption by modifying people’s perception of the amount of food being served; and the amount of food they consume. The practical study was based on the integration of three main aspects of creative design of packaging; environmental aspect (using local environmental materials), economical aspect (using economically inexpensive materials and ideas) and the creative aspect (relying on unusual ideas that are not used in the Egyptian society), hence; the exquisiteness factor is based on the idea, assemblage and printing methods. The problem of this research emerges from the need to set techniques to utilize the local environmental materials with an economic perspective that accomplishes distinctive aesthetic and design values. The research aims to discover the economics of creative utilization of the environmental materials in packaging, it is based on the hypothesis which proclaims that attempting to use and utilize the environmental materials in packaging in a creative way; will induce creation of new packaging methods that obtain the environmental aspect and hold evident economical outputs.
Keywords: التعبئة التغليف -- تغليف المنتجات -- التصميم الإبداعي